Komunikasi Dakwah dalam Novel âHabibie & Ainunâ Karya Bacharuddin Jusuf Habibie (Analisis Gender) - Rahmah, Mariyatul Norhidayati (IAIN Antasari Banjarmasin, 2014)
Gender Issues is still a thing inherent in family life. It also can be found, in the social construction, attitudes that are unfavorable to women, like for example women marginalization, womenâs position subordination, or womenâs labeling that they are irrational. Those treatments have made women losing their rights in the decision-making in the family or social life. Thus, various efforts are needed to improve gender equity. The communication of Dakwah in the novel of Ainun and Habibie can be one of the efforts to achieve it. The novel of Ainun and Habibie firmly reflects Habibieâs attitudes and perspective on gender. His expression of appreciation and respect to women is clearly pictured in the sentence like: âhidden behind the success of a figure two important womenâs roleâa mother and a wife. Habibie, quoting Ainunâs expression: âThe big you and the small Iâ, clearly describes Ainun as a wife who can create harmony and balance in their family life, and with her modesty giving the front position to her husband. The âArkâ of Habibie and Ainun has managed to shift the state of the familyâfrom nothing to everything, in many ways.